2010
DOI: 10.1159/000295904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a System for Transcutaneous Long-Term Capnometry

Abstract: Background: The measurement of CO2 partial pressure (PCO2) is of great importance. Former systems of transcutaneous capnometry combining the measurement of oxygen partial pressure (PO2) and PCO2 had their limitations due to skin irritations caused by the heating-up of the sensor and a short application time of 4 h. Objectives: To evaluate for the first time combined monitoring of transcutaneous PCO2 (tcPCO2) and oxygen saturation applying a lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Using the same methodology on a limited number of patients, 4 studies found lower levels of drift [16,22,23,26]. Another study performed on 29 healthy individuals found no significant drift during continuous 4 h PtcCO 2 recordings [45].…”
Section: Discussionmentioning
confidence: 85%
“…Using the same methodology on a limited number of patients, 4 studies found lower levels of drift [16,22,23,26]. Another study performed on 29 healthy individuals found no significant drift during continuous 4 h PtcCO 2 recordings [45].…”
Section: Discussionmentioning
confidence: 85%
“…Our studies 21 are the only studies to examine transcutaneous capnography via the comparison of capillary instead of arterial blood gas measurement with P tcCO 2 . This is important because of its impact on routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, a 6-min walk test and a cycle ergometer exercise test were performed whenever possible.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…These have looked at critically ill children,[15] emergency room patients with acute respiratory failure,[16] patients during cardiopulmonary exercise testing,[17] or healthy individuals. [18] Two previous studies have evaluated critically illness patients:[47] the first one[4] looked at eighteen patients, among whom, nine had hemodynamic instability treated with inotropic or vasoactive drugs; the second study[7] evaluated 69 critically ill patients admitted to the surgical intensive care unit for major surgery, multiple trauma, or septic shock. Of this group, 39 were placed on mechanical ventilation.Only three further studies have evaluated transcutaneous monitoring in patients undergoing non-invasive ventilation: the first two[1617] (with a small number of patients) had a good agreement between PaCO 2 and PtCO 2 , the third,[5] instead, reported a sub-optimal result.…”
Section: Discussionmentioning
confidence: 99%